Single-cell atlas of the first intra-mammalian developmental stage of the human parasite Schistosoma mansoni - Carmen Lidia Diaz Soria (Nature Portfolio, 2020)
Schistosomes undergo several develepmental stages during infection of humans. Here, the authors perform single-cell RNA sequencing on the earliest intra-mammalian stage of Schistosoma mansoni and generate a comprehensive cell-type atlas for this human parasite.